Dermatologic Presentation of Intrahepatic Cholestasis in Pregnancy: A Meta-Analysis Linking Serum Bile Acids, Pruritus, and Neonatal Outcomes - Dr Bakhtawar,Dr Anum shakeel ,Dr. Mehreen Abbas ,Dr Alveena fareed ,Dr Saadia karim ,Dr Aayesha Butt ,Dr Amber Shams, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Intrahepatic cholestasis of pregnancy (ICP) is a liver disorder found only in pregnancythat results from a mulitfactorial interplay of genetic, hormonal, and environmentfactors. Dysfunction in hepatocellular transport systems causes impaired bile acid